2019
DOI: 10.1002/celc.201900688
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing Charge Recombination and Ultraviolet Light Degradation of Perovskite Solar Cells Using Silicon Oxide Passivation

Abstract: Organic‐metal lead halide perovskite solar cells (PSCs) featuring low‐cost and high efficiency have been recognized as promising photovoltaic devices, but their serious charge recombination and ultraviolet light irradiation instability limit their output efficiency and long‐term operation. In this work, we have introduced silicon oxide as an interfacial modifier of the electron transporting layer in TiO2‐based planar heterojunction PSCs. The incorporation of a silicon oxide modifier passivates the trap states … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 75 publications
(92 reference statements)
1
35
0
Order By: Relevance
“…prepared a mixed halide Pb based perovskite and the developed perovskite solar cells (PSCs) device exhibited an highest PCE of 19.33 % and highest PCE of 23 % was certified by NREL . However, in general low stability and highly toxic nature of Pb restricted production at large scale for commercialization . Thus, Hou et al .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…prepared a mixed halide Pb based perovskite and the developed perovskite solar cells (PSCs) device exhibited an highest PCE of 19.33 % and highest PCE of 23 % was certified by NREL . However, in general low stability and highly toxic nature of Pb restricted production at large scale for commercialization . Thus, Hou et al .…”
Section: Methodsmentioning
confidence: 99%
“…employed Fe 2 O 3 /PCBM electron transport layer and the fabricated device showed the improved stability with interesting PCE of 14 % . This suggested that the stability could be improved by introducing some novel electron transport/charge extraction layers but the presence of Pb remains a challenge . In this regard, tin (Sn) was introduced as a suitable replacement for Pb due to its similar valency, ionic radii and less toxicity .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…With the rapid development of industry, materials, energy, printing and agriculture, a large amount of sewage and other pollutants is directly discharged without being purified or purification treatment . This fails to meet the discharge standards and causes severe damages to the water environment.…”
Section: Introductionmentioning
confidence: 99%